Multi-band notched circular polarized MIMO antenna for ultra-wideband applications - Thakur, Ekta; Jaglan, Naveen; Gupta, Anupma; Al Gburi, Ahmed Jamal Abdullah (Electromagnetics Academy, 2024)
This paper details the development of an innovative Ultra-Wideband (UWB) Circularly Polarized (CP) Multi-Input MultiOutput (MIMO) antenna. Drawing inspiration from an Electromagnetic Band-Gap Structure, the antenna incorporates Two Via Compact Electromagnetic Band Gap (TVCEBG) cells strategically positioned close to the feedline. The result is a sophisticated triple-band notched planar antenna configuration. To enhance its performance, a slot and a stub are strategically added to the bottom plane, effectively broadening the Axial Ratio Bandwidth (ARBW). This carefully designed setup achieves a wide ARBW while simultaneously rejecting interference at 3.5, 5.5, and 8.2 GHz. Notably, the MIMO antenna demonstrates an axial ratio spanning from 3 to 10.4 GHz, coupled with an impedance bandwidth ranging from 3.1 to 10.6 GHz. Diversity features of the proposed structure are quantified through three key parameters: ECC (Envelope Correlation Coefficient) greater than 0, TARC (Total Active Reflection Coefficient) surpassing 10, and DG (Diversity Gain) exceeding 9.7. These parameters collectively indicate robust diversity characteristics, underscoring the antenna’s efficacy in challenging communication scenarios. Practical implementation involves the use of FR4 dielectric substrates, with precise measurements of 42.7 × 55 × 1.6 mm3. This meticulous construction ensures the realization of the proposed structure’s theoretical framework, highlighting the antenna’s potential applicability in advanced UWB communication systems.